Thermal Decomposition of Ternary Sodium Graphite Intercalation Compounds. Issue 29 (7th April 2020) - Au, Heather; Rubio, Noelia; Buckley, David J.; Mattevi, Cecilia; Shaffer, Milo S. P.
Abstract: Graphite intercalation compounds (GICs) are often used to produce exfoliated or functionalised graphene related materials (GRMs) in a specific solvent. This study explores the formation of the Na‐tetrahydrofuran (THF)‐GIC and a new ternary system based on dimethylacetamide (DMAc). Detailed comparisons of in situ temperature dependent XRD with TGA‐MS and Raman measurements reveal a series of dynamic transformations during heating. Surprisingly, the bulk of the intercalation compound is stable under ambient conditions, trapped between the graphene sheets. The heating process drives a reorganisation of the solvent and Na molecules, then an evaporation of the solvent; however, the solvent loss is arrested by restacking of the graphene layers, leading to trapped solvent bubbles. Eventually, the bubbles rupture, releasing the remaining solvent and creating expanded graphite. These trapped dopants may provide useful property enhancements, but also potentially confound measurements of grafting efficiency in liquid‐phase covalent functionalization experiments on 2D materials. Abstract : Producing graphene : Graphite intercalation compounds (GICs) are often used to produce exfoliated or functionalised graphene related materials (GRMs) in a specific solvent. This study explores the formation of the Na‐tetrahydrofuran (THF)‐GIC and a new ternary system based on dimethylacetamide (DMAc).